THE IMPLEMENTATION OF LIVING HADITH TO INCREASE THE LEARNING MOTIVATION OF CHILDREN WITH SPECIAL NEEDS - Setyaningrum, Putri Nadha; Mandar, Yasri (UIN Antasari Banjarmasin, 2024)
Children with special needs often face various challenges in the learning process, such as communication barriers, difficulties in social interaction, and problems adjusting to the learning environment. This paper aims to find out how the application of hadith values in writing, speaking and practicing by teachers is an important strategy to encourage children with disabilities to overcome these problems and develop their full potential. The research methodology used is descriptive qualitative, which produces descriptive data that can be observed from the words or speech of participants. This research method was conducted directly in the field (field research) with data collection techniques through observation, interviews and documentation. This research was conducted on May 3, 2024 at SLB Bhakti Kencana 1 Berbah. The results showed that in SLB Bhakti Kencana 1 Berbah the application of hadith about learning motivation was carried out through writing, oral and practice. Providing strong learning motivation to children with special needs is very important because it can help them overcome the various problems they face. High learning motivation can help children with special needs stay motivated, confident and excited in facing learning challenges